Shill Bidding and Information in Sequential Auctions: A Laboratory Study - Jim Ingebretsen Carlson; Tingting Wu (Lund University, School of Economics and Management, Department of Economics, 2018)
Second-price auctions with public information, such as those on eBay, provide an opportunity for sellers to use the information from finished and ongoing auctions when acting strategically in future auctions. Sellers have frequently been observed to bidding on their own item with the intent to artificially increase its price. This is known as shill bidding. Using lab experiments with two sequential auctions, we study the effect of shill bidding when the seller can choose to shill bid in the second auction. We also study the impact of different information revelation policies regarding the provision of the first auction bidding history to the seller. The experimental data confirm that shill bidding in the second auction affects outcomes in both auctions. Our findings are consistent with the predictions that the threat of shill bidding in the second auction does increase the bidders' final bid in the first auction. However, providing the seller with the bidding history from the first auction does not affect any important outcome variables.
Keywords: C92; D03; D44; 330; Sequential auctions; shill bidding; experiment